The last century of the Chora Monastery: a new look at the tomb monuments - Melvani, Nicholas ca. 20./21. Jh. (Byzantinische Zeitschrift, 2021)
The present article re-examines the tomb monuments in the parekklesion and the outer narthex of the main church of the Chora monastery, which are generally thought to date from the early Palaiologan period. Based on the analysis of the iconography and style of the frescoes adorning the tombs, it is suggested that some of the burials should be re-dated at least a few decades later. The frescoes in the lunette of the Tomb of Michael Tornikes (Tomb D) appear to have been executed shortly after 1350 and the decoration of Tombs C and E must date from around the same time. The portraits in Tombs F and G date from the 15th century. The epigraphic evidence and the images illustrate the continuing use of the Chora by its patrons, members of various branches of the Tornikes, Asanes, Raoul, and Dermokaites families, during the last century of the monastery.